Music and Spirituality - Thérèse Smith (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Across time and geography people have known the power of music for evoking the gods and acquiring spiritual insight. Whether arising as a textless chant by a single voice or a percussive auditory context for ritual dance, music in its various modes is a virtually ubiquitous companion to religious and spiritual practices. The apparently intangible, insubstantial nature of sound is one of the reasons why music has so effectively symbolized the mysterious and wholly other since the dawn of creation. Not only an accompaniment to one's spiritual trek, musical compositions from the great oratorios of Handel to the soundtrack to the movie Lord of the Rings also serve as powerful metaphors and inspirations for that journey.